If you don't succeed, should you try again? The role of entrepreneurial experience in venture survival - Sandra Gottschalk; Francis J. Greene; Daniel Höwer; Bettina Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
There remains considerable scholarly debate about the role that prior entrepreneurial experience plays in new venture survival. Drawing on entrepreneurial learning theories, we use panel data on 8,400 new ventures to investigate the impact of four different types of prior entrepreneurial experience (portfolio, serial, failure (bankruptcy/voluntary dissolution) and a mix of success (portfolio/serial) and failure (prior bankruptcy/dissolution) on venture survival outcomes. We find that previously failed entrepreneurs are less likely to survive and, in common with entrepreneurs with mixed prior experiences, are more likely to experience bankruptcy. We find that portfolio and serial experience is unrelated to survival or avoiding bankruptcy. Conclusions for entrepreneurship scholars, entrepreneurs and stakeholders are discussed.
Keywords: L26; L25; 330; venture survival; entrepreneurial experience; panel data